Hepatoprotective and hypoglycemic effects of a tannin rich extract from Ximenia americana var. caffra root - Sobeh, Mansour; Mahmoud, Mona Fouad; Abdelfattah, Mohamed A. O.; El-Beshbishy, Hesham A.; El-Shazly, Assem; Wink, Michael (Phytomedicine, 2017)
Background